IMPLEMENTASI MANAJEMEN PENDIDIKAN ISLAM DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMK SETIA BHAKTI KECAMATAN TANJUNG RAYA KABUPATEN MESUJI - Hartoyo; Sulthan Syahrir; Dewi Yanti; Ari Supadi (UNISAN JURNAL, 2023)
Education management is needed to ensure that all educational activities can be carried out optimally, so that the quality of education in these schools can be further improved. The benchmark of the implementation of education management is the success of the implementation of the four management functions, namely planning, organizing, implementing, and monitoring activities. If a school is able to properly carry out the four functions of education management, the achievement of the quality of education will be more optimal as well. Based on the results of the author’s pre-survey at SMK Setia Bhakti Jaya on the Implementation of Education Management, it is Enough, But the Quality of Education at SMK Setia Bhakti is still not optimal, such as: there are still teachers who carry out learning activities that do not activate students, there are still teachers who are lacking utilizing existing learning media in sekolah, there are still excellent students whose academic achievements are less than satisfactory. For this reason, the authors are interested in conducting further research on "Implementation of Educational Management in Improving the Quality of Education", with the research location at SMK Setia Bhakti. The problems in this research are: how is the implementation of education management in improving the quality of education at SMK Setia Bhakti . The research objective is to determine the implementation of education management in improving the quality of education at SMK Setia Bhakti . To answer these problems, data collection uses participatory observation techniques, unstructured interviews and documentation. The data analysis technique was carried out in three stages, namely data reduction, data presentation, and data verification, which were then described in a descriptive narrative. The findings of this study are: with the implementation of education management through the function of planning, organizing, mobilizing, and controlling which is quite good, the quality of education in terms of sources, processes and learning outcomes at SMK Setia Bhakti can be even better. This means that the implementation of education management can improve the quality of education at SMK Setia Bhakti .